Una tipologia de la definició lexicogràfica aplicada al «DGLC» - Alsina, Victòria; Sol, Lluís; Soler, Joan (Caplletra. Revista Internacional de Filologia, 2015)
This article aims at establishing a typology of lexicographic definitions by means of the study of the definitions found in Pompeu Fabra’s Diccionari General de la Llengua Catalana in nouns, verbs and adjectives. Several typologies based on different criteria are arrived at: in the first place, the difference between synthetic and periphrastic definitions is established; this classification is based on the amount of words used in the definition. In the second place, the typology which comprises substantial and relational definitions is explained; it was established by Rey-Debove (1967) and it is based on the metalanguage used in the definition. And thirdly, a classification within substantial periphrastic definitions is established, based on the defining words used: lexical and semo-componential definitions.